One-year resource utilisation, costs and quality of life in patients with acute respiratory distress syndrome (ARDS): secondary analysis of a randomised controlled trial. Issue 1 (December 2016) - Marti, Joachim; Hall, Peter; Hamilton, Patrick; Lamb, Sarah; McCabe, Chris; Lall, Ranjit; Darbyshire, Julie; Young, Duncan; Hulme, Claire
Abstract Background The long-term economic and quality-of-life outcomes of patients admitted to intensive care unit (ICU) with acute respiratory distress syndrome are not well understood. In this study, we investigate 1-year costs, survival and quality of life following ICU admission in patients who required mechanical ventilation for acute respiratory distress syndrome. Methods Economic analysis of data collected alongside a UK-based multi-centre randomised, controlled trial, aimed at comparing high-frequency oscillatory ventilation with conventional mechanical ventilation. The study included 795 critically ill patients admitted to ICU. Hospital costs were assessed using daily data. Post-hospital healthcare costs, patient out-of-pocket expenses, lost earnings of survivors and their carers and health-related quality of life were assessed using follow-up surveys. Results The mean cost of initial ICU stay was £26, 857 (95 % CI £25, 222–£28, 491), and the average daily cost in ICU was £1738 (CI £1667–£1810). Following hospital discharge, the average 1-year cost among survivors was £7523 (CI £5692–£9354). The mean societal cost at 1 year was £44, 077 (£41, 168–£46, 985), and the total societal cost divided by the number of 1-year survivors was £90, 206. Survivors reported significantly lower health-related quality of life than the age- and sex-matched reference population, and this difference was more marked in younger patients. Conclusions Given the high costs and low health-related quality of life identified, there is significant scope for further research aimed at improving care in this in-need patient group. Trial registration ISRCTN10416500